PROGRAM PENDIDIKAN KESETARAAN PAKET A SEBAGAI PENDIDIKAN ALTERNATIF DI LINGKUNGAN PESANTREN - Wijayanti, Intan (PREMIERE : Journal of Islamic Elementary Education, 2022)
Education is a way of man towards a more dignified life. In UU Sisdiknas No. 20 of 2003, that one form of non-formal education is equality education. This research to find out about the Package A equivalence education program as an alternative education in pesantren. The research location at PKBM Ibnu Ali Sidoarjo, this study used a qualitative research method with a case study. Data was collected through observation, interviews, and documentation. Data analysis includes data reduction, data presentation, and verification or conclusion. The results of this study are the birth of the Package A equality education program PKBM Ibnu Ali at Ma'had Ibnu Ali started with the caregiver's desire to facilitate his students to get general education; the existence of the PKBM Ibnu Ali is considered very appropriate as an alternative education in Ma'had Ibnu Ali on the grounds that the curriculum is adaptive, flexible, and independent. Factors supporting the existence of PKBM Ibnu Ali include a curriculum that is integrated with the Qur'an; the academic qualifications of the tutors; the location is in pesantren; solid teamwork; and positive response from students and their parents. While the inhibiting factors are the limited infrastructure, media and learning resources; students of different levels are still made into one class; limited stakeholder; and Ma'had locations scattered in several locations stakeholders.